A study on the effect of personal conflict towards learning and conflict management among semester 8 TESL students in UiTM Shah Alam / Ku Aminur Zafflasnul Ku Yin - Ku Yin, Ku Aminur Zafflasnul (Faculty of Education, 2012)
None can deny that conflict is a part of life. Conflict will always take place in one's life in all kinds of human relationships and in all social settings. A person with good management of conflict will reasonably be able to live a better life compared to a person with unstable of poor management of conflict.It is obvious that conflict within oneself plays an important role in determining their way to success in academic and life as well. Life is a roller-coaster ride with its ups and downs thus it is important for students to have the awareness on conflict management. 40 semester 8 TESL students from Faculty of Education, UiTM Shah Alam have participated in this study. This study intended to find out on a) What is the most common personal conflict among semester 8 TESL student; b) What are the most common effects of personal conflict towards learning; c) How semester 8 TESL students manage their personal conflict d) What is the coping mechanism used by semester 8 TESL students in resolving their personal conflict; e) What is the level of personal conflict management among semester 8 TESL students. The findings of this research are a) Most of the semester 8 TESL students are having obstacles in certain subjects in TESL, b) Lost of confidence and the feeling of uneasiness are the most common effect of personal conflict towards learning, c) Berational and calm during a conflict is the most preferred personal conflict management practiced by most semester 8 TESL students, d) Get help from other people is the coping mechanism used by semester 8 TESL students in resolving their personal conflict, e) The level of personal conflict managementamong semester 8 TESL students is in moderate level.